Dual mobility articulation total hip arthroplasty for displaced neck fracture in elderly with neuromuscular disorder. Issue 6 (June 2021) - Ryu, Hyung-Gon; Roh, Young Ju; Oh, Kwang-Jun; Hwang, Ji-Hyo; Kim, Yeesuk; Cho, Hyun-Woo; Kim, Sang-Min
Highlights: THA with dual mobility articulation is a reasonable treatment option for femoral neck fractures with neuromuscular diseases. Abstract: Purpose: Neuromuscular disease is well known to be at increased risk of complications following hip replacement surgeries. This study is prospectively conducted to investigate clinical performance and survivorship of total hip arthroplasty (THA) using dual mobility articulation in femoral neck fractures of elderly with neuromuscular disease. Materials and Methods: We prospectively enrolled 162 patients (162 hips) with displaced femoral neck fracture who gave informed consent for dual mobility articulation THA. Of the 162 patients, 35 patients had neuromuscular disease including cerebral palsy, poliomyelitis, hemiplegia, and Parkinson disease (NM group). The other 127 patients had no history of neuromuscular disease (non-NM group). The mean age was 76.5 years (range, 60 – 95) and female ratio was 71.0% (115/162). Clinical outcomes including Harris hip score (HHS), University of California Los Angles activity (UCLA) score were compared between the two groups. Computed tomography and serial radiographs were obtained after surgery. Postoperative complications and reoperation including revision were recorded. Results: Pain-VAS and all clinical scores of the NM group were comparable to those of the non-NM group. The incidence of dislocation in the NM group did not differ from that in Non-NM group (2/35, 5.7% versus 5/127, 3.9%, p = 0.645). Reoperation was performed in 3 hips (3/35, 8.6%) of the NM group and in 4 hips (4/127, 3.1%) of the non-NM group ( p = 0.173). Kaplan-Meier survivorship with an end point of revision for any reason was 97.1% (95% confidence interval [CI], 0.92 to 1.03) in the NM group and 98.4% (95% CI, 0.96 to 1.01) in the non-NM group at 7.3 years after surgery. Conclusions: In elderly with neuromuscular disease, THA with dual mobility articulation is a reasonable option as a treatment for femoral neck fractures.